1985
DOI: 10.1128/mcb.5.11.3084
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus serotype determines association and localization of the large E1B tumor antigen with cellular tumor antigen p53 in transformed cells.

Abstract: The distribution and stability of the cellular tumor antigen p53 were studied in baby rat kidney cells transformed by region El sequences of nononcogenic adenovirus (Ad) type 5 (Ad5) or oncogenic type 12 (Adl2). In transformed cells expressing the large ElB T antigen of AdS, p53 was associated with this T antigen. The complexed proteins were concentrated in a cytoplasmic body, which has been shown to consist of a cluster of 8-nm filaments (A. Zantema et al., Virology 142:44-58, 1985). In transformed cells expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
114
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 33 publications
12
114
1
Order By: Relevance
“…In the AdBRK cells used for this study, WT1 exclusively localizes to the nucleus (data not shown), probably due to the fact that these cells were transformed with the E1A region of adenovirus type 5 and the E1B region of adenovirus type 12. The large E1B protein of adenovirus type 12 appears not to bind to p53 (Zantema et al, 1985). These results all indicate that the eects of WT1 are modulated by other factors in addition to a possible eect of p53.…”
Section: Discussionmentioning
confidence: 49%
“…In the AdBRK cells used for this study, WT1 exclusively localizes to the nucleus (data not shown), probably due to the fact that these cells were transformed with the E1A region of adenovirus type 5 and the E1B region of adenovirus type 12. The large E1B protein of adenovirus type 12 appears not to bind to p53 (Zantema et al, 1985). These results all indicate that the eects of WT1 are modulated by other factors in addition to a possible eect of p53.…”
Section: Discussionmentioning
confidence: 49%
“…This apparent sequestration within a single cytoplasmic structure is a striking feature of the physical association between E1B 55K and host cell proteins, providing a dramatic illustration of the ability of a viral oncoprotein to inactivate a tumor suppressor gene product (Zantema et al, 1985a). Formation of this cellular structure has been observed with adenovirus serotype 5, whose E1B 55K protein binds p53, but not with serotype 12, whose corresponding E1B 54K protein fails to interact directly with p53 (Zantema et al, 1985b;van den Heuvel et al, 1993). The mechanism underlying formation of the cytoplasmic body and its exact composition are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst Ad E1B 54K and 58K proteins share the ability to neutralize p53 there are a number of striking di erences between them. The Ad2/5 proteins bind p53 strongly (Sarnow et al, 1982;Zantema et al, 1985a) with the p53/Ad E1B complex being localized to cytoplasmic dense bodies in Ad2/5 E1-transformed cells (Zantema et al, 1985b;Blair-Zejdal and Blair, 1988). In contrast, Ad12 E1B 54K interacts with p53 only weakly (Grand et al, 1994).…”
Section: Introductionmentioning
confidence: 99%